Sistema produto-serviço: uma análise interdepartamental nas indústrias química e automotiva - Rocha, Mauro Vinicius Silva (Universidade do Vale do Rio dos Sinos, 2014)
The present study investigates alternatives for the improvement of product-service system. A multiple case study involving eight national and multinational companies, from chemical and automotive industries, was conducted. In these organizations the internal problems that affect the performance of the provision of services associated with the product were analyzed. For each problem identified alternatives implemented, or likely to be adopted solution were analyzed. The results point to a set of internal processes, which focus attention only to the demands from products. Consideration of these results unveiled a set of elements that need to be considered for the improvement of product-service system.
Keywords: Serviços; Serviços industriais; Servitização; Infusão de serviços; Sistema produto-serviço (SPS); Services; Industrial services; Servitization; Infusion of service; Product-service system (PSS); ACCNPQ::Engenharias::Engenharia de Produção